(untitled) (Bangladesh Journal of Pharmacology, 2016)
To improve efficacy of non-invasive positive pressure ventilation (NPPV), this study investigated the combination of NPPV with naloxone in COPD patients with respiratory failure. One hundred four patients with COPD-related respiratory failure were enrolled prospectively and randomly divided into a control group treated with NPPV alone (n = 52) and an observation group treated with NPPV combined with 4.0 mg naloxone by continuous infusion (n = 52). At 3 and 5 days after the start of treatment, the respiratory mechanics, pulmonary function, and oxygen metabolism parameters were significantly improved in the NPPV + naloxone group compared to the NPPV alone group (p<0.05). Further, the improvements in the NPPV plus naloxone group were greater at day 5 than at day 3 (p<0.05). These findings indicate that non-invasive positive pressure ventilation combined with naloxone can more effectively improve respiratory mechanics, pulmonary function and oxygen metabolism of COPD patients with respiratory failure than NPPV alone, offering a new treatment approach.